System analysis of technological process of bread making - Швед, Сергій Миколайович; Ельперін, Ігор Володимирович (Eastern-European Journal of Enterprise Technologies, 2012)
The article outlines the issues necessary for the implementation of modern methods of automatic control and management of technological process of bread making in order to improve the high quality of bakery products. To determine the scope of work for the improvement of the management process of bread making we carried out a systematic analysis of the technological process of bread production and systems of management applying SADT (Structured Analysis and Design Technique). The diagrams of bakery production process show that each previous block affects the following according to two streams: the material flow of semi-product and the data array describing the progress of each stage, and that can be used by an experienced operator to correct technological modes of the next stage, which is very important for management of bakery products production, as each stage, in accordance with production schedules, must be completed by obtaining the semi-product with relevant technological parameters. The analysis showed that the quality of the finished product depends on the quality of flour and operational changes of process parameters at different stages of production, depending on the quality of the manufacturing operations at each previous stage of production. Taking into consideration the complexity of the technological processes of baking the existing automation system should be supplemented with subsystems of decision-making support using the methods and algorithms of fuzzy logic